+0  
 
0
561
3
avatar+516 

Enter a recursive rule for the geometric sequence.

6, −18, 54, −162, ...

 

a1=___ ; an= ___

 Mar 18, 2019
 #1
avatar+111390 
+1

The common ratio is       -18 / 6  = -3

 

a1  =  6

an  =  6(-3)n-1    =   explicit rule

 

The recursive rule is

 

an =  an-1 (-3)

 

cool coolcool

 Mar 18, 2019
 #2
avatar+516 
+1

Im a little confused.. so how would i fill in this blank then:  a1=__?__ ; an= __?__

kikidylm  Mar 18, 2019
 #3
avatar+111390 
0

a1  =  the first term     = 6

 

an   =  the nth term  =   a1 (-3)n - 1

 

For example.....the second term is

 

a2  =  6 (-3)2-1   =  6(-3)1  =  6 * -3   =  - 18

 

cool cool cool

CPhill  Mar 18, 2019

10 Online Users

avatar
avatar